ADAR1 Alleviates Inflammation in a Murine Sepsis Model via the ADAR1-miR-30a-SOCS3 Axis. (24th March 2020) - Shangxun, Zhou; Junjie, Li; Wei, Zhao; Yutong, Wang; Wenyuan, Jia; Shanshou, Liu; Yanjun, Wang; Qianmei, Wang; Zhusheng, Feng; Chaoping, Yu; Ran, Zhuang; Wen, Yin; et al.
Abstract : Adenosine deaminase acting on double-stranded RNA 1 (ADAR1) mediates adenosine-to-inosine (A-to-I) RNA editing events. ADAR1 is highly expressed in "septic" macrophages and in small intestinal tissues of mice with sepsis. Overexpression of ADAR1 suppresses inflammation and intestinal damage. However, the specific underlying mechanism is unclear. This study was conducted to explore how microRNA (miRNA) regulates the anti-inflammatory mechanism of macrophages following ADAR1 upregulation. A murine sepsis model was established by cecal ligation and puncture (CLP). Mice were randomly assigned to sham, CLP, and CLP+ADAR1 groups. Hematoxylin and eosin (HE) staining and fluorescence isothiocyanate-dextran were used to evaluate intestinal injury and permeability. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR), western blotting, and Luminex assays were performed to detect changes in the expression of inflammatory cytokines. Adenoviruses were used to express ADAR1 in RAW 264.7 cells. Ribonucleoprotein immunoprecipitation analysis was conducted to detect the binding of ADAR1 and miRNAs. A dual-luciferase reporter assay was used to detect the binding of miRNAs and regulatory factors. We observed that ADAR1 significantly increased the expression of suppressor of cytokine signaling 3 (SOCS3) in macrophages and reduced the expression of interleukin-6 in macrophages and the serum, thereby reducing intestinal permeability and mucosal injury in mice with sepsis. The RNA-ribonucleoprotein immunoprecipitation binding assay and qRT-PCR demonstrated a direct interaction between ADAR1 and pri-miR-30a. The luciferase assay demonstrated that SOCS3 was significantly inhibited by miR-30a-5p, the mature product of miR-30a. Thus, ADAR1 exerts a protective effect against sepsis by reducing inflammation and organ damage via the ADAR1-miR-30a-SOCS3 axis.